2017
DOI: 10.18524/1810-4215.2017.30.114670
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Emission of Solar Flares: Coronal Mass Ejections and Shock Waves

Abstract: ABSTRACT. Coronal mass ejections (CMEs) mostly affect the geomagnetic field. These structures are observed and studied with coronagraphic images therefore we don't see the corona in the plane of the sky and the measurements of the propagation speed for solar disk events are not accessible to coronagraphic observations. This suggests that microwave emission of solar flares that can be attributed to the gyrosynchrotron mechanism of mildly relativistic electrons can be used. In turn, the relationship between coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…The estimation of CME magnetic fields can be diagnostic based on radio observations [3], [4]. Connection between CMEs and solar radio events has been studied earlier.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of CME magnetic fields can be diagnostic based on radio observations [3], [4]. Connection between CMEs and solar radio events has been studied earlier.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, two bands can be distinguished corresponding to the main and second harmonics. In this work, we used a new regression model (Isaeva and Tsap, 2017) to approximate the type II burst harmonics (1), where fi,j is the frequency of the maximum of type II burst at a given harmonic at a given time ti, ireference number, j -harmonic number, aj and dj -linear regression coefficients. c) The relationship between the proton flux intensity Ip and the frequency fi,1, min, at which the minimum value of the relative distance bi,min between the harmonics of the type II burst is observed.…”
Section: Initial Data and Research Resultsmentioning
confidence: 99%
“…Almost all proton events are accompanied by coronal mass ejections (CME). Earlier in the work (Isaeva & Tsap, 2017) it was shown that there is a strong relationship between the speed of the CME V CME and the integral flux of the continuum microwave bursts ∫F μ dt. Moreover, the connection between the speed of the CME and the integral flux of the continual radio bursts of the IV type weakens with a decrease in the frequency of the burst of the IV type and is practically absent already in the meter-decameter range.…”
Section: Relationship Between the Intensity Of The Proton Flux I P Anmentioning
confidence: 98%